Ivabradine reversed nondipping heart rate in rats with l‐NAME‐induced hypertension. (28th March 2019) - Baka, Tomas; Simko, Fedor
Summary: We hypothesized that decreasing elevated night‐time heart rate (HR) in hypertension by administering a bradycardic agent (ivabradine) at bedtime could bring cardiovascular benefit. Since rats are nocturnal animals, they exhibit circadian rhythms phase‐shifted relative to humans. Sixty‐six Wistar rats were divided into non‐diseased controls and rats withl ‐NAME‐induced hypertension to compare the haemodynamic effects of daytime‐dosed and night‐time‐dosed ivabradine.l ‐NAME‐induced hypertension inverted the physiological 5.6% night‐to‐day HR dip to an undesirable HR rise by 11.1%. Ivabradine dosed at daytime (the rat's resting phase) reverted a night‐to‐day HR rise to HR dip by 14.2%. These results suggest a cardiovascular benefit of ivabradine dosed at the human's resting phase (night‐time) for hypertensive patients with nondipping HR.